Positioning and the Thick Tangles of Spacetimemattering. (March 2023) - Davies, Bronwyn
This paper re-turns to the concept of positioning, and to the thick tangles of spacetimemattering as they were at work in the paper "Positioning: the discursive production of selves" by Davies & Harré, published in 1990. In re-turning to the concept of positioning, and to its analysis, this paper asks what matters in scholarly work, and how it contributes to gendered, colonial relations of power. The paper explores the impact of the spacetimes scholars work in, on their thinking-in-being.